Understanding the Phenomenon of Violence: A Perspective of Philosophical Anthropology - Paul Rohan, J.C. (Journal of Don Bosco Institute of Philosophy and Humanities, 2018)
In the present human society, the omnipresent violence reaches and strikes all the human beings in the forms of crimes, wars, massacres and by its daily pressures. The phenomenon of violence is present even from the womb of the mother when the human being is in the state of a foetus. Is it not advisable to admit that violence is in the root of the human nature? Such an understanding of violence is anthropological and there is an urgency to formulate the concept of ‘homo violens’ (violent man) together with other fields like morality, philosophy, sociology, etc. Considering the human being as ‘homo violens’ is not to support or encourage violent activities, but to face the reality of human nature and to accept that man is intrinsically violent. This will bring an acceptance on the part of human beings about their reality and help them deal with this grave issue. The anthropological studies have purposely avoided facing the reality of human violence in order to adhere to the traits of civilization which consider human life, human body and human actions as sacred and have higher motives. However, the human reality is violent and the human race has to admit this fact and still move towards a civilization which is shattered of all its traits of brutalities. There is an inevitable fact that there is only a subtle difference between cannibalism and civilization. The study or serious examination of ‘homo violens’ (the violent man), will also contribute to the study of ‘homo pācātus’ (the non-violent man) who has to still arrive in the human history.
Keywords: Aggression; Human rights; Intentional; Homo animalis; Homo Pācātus; Homo Violens; Perpetrator; Predatory; Repression; Victims